sychological effects and their impact on university students in Libya الآثار النفسية وتأثيرها على طلبة الجامعة في ليبيا - Saada Ali Khalifa سعدة علي خليفة (Journal Of Babylon Center For Humanities Studies, 2020)
University students with different specializations are exposed to different psychological, social and academic pressures that differ according to their specializations and circumstances, and these pressures may have a negative impact on the student in various academic and psychological aspects at the present time after the revolution in Libya, and psychological pressures are a phenomenon of human life that the individual tells in different situations and times , And human life is troubled as a result of disparate changes, it is not free of tension and distress, and the tension resulting from the psychological pressures faced by those who live in a rapidly changing world (). Students face some stressful factors, such as inflexible curricula that are taught to all students in the same way without taking into account the individual differences between them and without looking at their inclinations and preparations, so the curricula and teaching methods become in vain for some students, in addition to the parents ’ambitions related to the son’s future may exceed the capabilities and capabilities of this son And his preparations, and then the parents live a great concern regarding the future of their son, this anxiety that is transmitted to the son, because he lives struggles between his desire to achieve ambitions and his inability to achieve these aspirations and capabilities, and it is known that the widening gap between the level of development H and the level of capabilities is one of the reasons for the emergence of this psychological disorder. يتعرض طلاب الجامعات باختلاف تخصصاتهم إلى ضغوط نفسية واجتماعية وأكاديمية مختلفة تختلف باختلاف تخصصاتهم وظروفهم ، وهذه الضغوط قد يكون لها تأثير سلبي على الطالب بمختلف الجوانب الأكاديمية والنفسية في الوقت الراهن بعد الثورة في ليبيا ، والضغوط النفسية ظاهرة من ظواهر الحياة الإنسانية يخبرها الفرد في مواقف وأوقات مختلفة ، والحياة الإنسانية مضطربة نتيجة التغيرات المتباينة ، فهي لا تخلو من التوتر والضيق ، والتوتر الناشئ عن الضغوط النفسية التي يواجهها من يحيا في عالم سريع التغير ( ). يواجه الطلاب بعض العوامل الضاغطة ، كالمناهج غير المرنة التي تدرس لجميع الطلاب بالطريقة نفسها دون مراعاة للفروق الفردية بينهم ودون النظر إلى ميولهم واستعداتهم فتصبح المناهج الدراسية وطرق التدريس بذلك عبثاً على بعض الطلاب ، فضلاً عن أن طموحات الوالدين المتعلقة بمستقبل الابن قد تتخطى قدرات هذا الابن وإمكانياته واستعداداته ، ومن ثم يعيش الوالدان قلقاً شديداً يتعلق بمستقبل ابنهما ، هذا القلق الذي ينتقل إلى الابن ، لأنه يعيش صراعات بين رغبته في تحقيق الطموحات وبين عجزه عن تحقيق هذه الطموحات والإمكانيات ، ومن المعروف أن اتساع الهوة بين مستوى الطموح ومستوى الإمكانيات يعد سبباً من أسباب نشأة هذا الاضطراب النفسي ( ).